Body Mass Index Decline Is Related to Spinocerebellar Ataxia Disease Progression. Issue 5 (11th August 2017) - Diallo, Alhassane; Jacobi, Heike; Schmitz‐Hübsch, Tanja; Cook, Arron; Labrum, Robyn; Durr, Alexandra; Brice, Alexis; Charles, Perrine; Marelli, Cecilia; Mariotti, Caterina; Nanetti, Lorenzo; Panzeri, Marta; et al.
Abstract: Background: Spinocerebellar ataxias (SCAs) are dominantly inherited, progressive ataxia disorders. Disease progression could be preceded by weight loss. Objectives: We aimed to study the course of weight loss in patients who had the most common SCAs (SCA1, SCA2 SCA3, and SCA6). Additional objectives were to identify subgroups of weight evolution, to determine the factors influencing these evolutions, and to assess the impact of these evolutions on disease progression. Methods: In total, 384 patients from the EUROSCA prospective cohort study were analyzed who had SCA1, SCA2, SCA3, or SCA6 and at least 3 measurements of weight. Age was used as a time scale. Clinical outcomes were body mass index (BMI) and the Scale for the Assessment and Rating Ataxia (SARA), with scores ranging from 0 to 40. We used a linear mixed model to analyze the course of BMI and a latent class mixed model to identify subgroup BMI evolution. Results: Overall, BMI declined over time (−0.11 ± 0.03 kg/m 2 per decade; P = 0.0009). Three subgroups of BMI evolution were identified: "decreasing BMI" (n = 88; 23%), "increasing BMI" (n = 70; 18%) and "stable BMI" (n = 226; 59%). Patients in the decreasing BMI group were more severely affected at baseline with higher SARA scores and a higher frequency of non‐ataxia signs (especially motor symptoms) compared with those in the other groups. Weight loss was associated with faster disease progression (5.7 ± 0.7 SARA points per decade; P = 0.036). Conclusions: The current data have substantial implications for the design of future interventional studies in SCA, as they provide a basis for patient stratification and emphasize the usefulness of BMI as a biomarker for monitoring disease progression.